Epidemiology and Impact of Prior Musculoskeletal Injury and Orthopaedic Surgery on Draft Rank, Availability, and Short-term Performance in Major League Baseball: A Summary Analysis and Matched Cohort of 1890 Predraft Players. Issue 5 (3rd May 2019) - Ramkumar, Prem N.; Navarro, Sergio M.; Luu, Bryan C.; Haeberle, Heather S.; Karnuta, Jaret M.; Stearns, Kim L.; Soloff, Lonnie; Frangiamore, Salvatore J.; Schickendantz, Mark S.
Background: Despite the many reports of injury rates in Major League Baseball (MLB), little is known about the epidemiology or impact of prior musculoskeletal injuries and surgical procedures among players entering the MLB draft. Purpose: To determine the (1) epidemiology of all musculoskeletal injuries and surgical procedures among players entering the MLB draft, (2) impact of injury or surgery on draft rank, (3) impact of injury or surgery on availability within the first 2 years of play in the MLB, and (4) impact of injury or surgery on performance. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively reviewed 1890 medical records that were completed by MLB team physicians as preparticipation physical assessment prior to the draft from 2014 to 2018. Players were divided into 3 groups: noninjured, nonoperative, and operative. Draft status, overall draft rank, missed games, batting average, and earned run average for the first 2 seasons of MLB play were obtained for all available players. Players across all 3 groups were compared with linear, logistic, and beta regression models, controlling for age, position, injury status, and draft rank. Unadjusted differences among groups were assessed with 1-way analysis of variance. Results: Overall, 750 position players and 1140 pitchers were included, of whom 22.8% had no reported injury history; 48.8% reported injury treated nonoperatively; and 28.5% were treated operatively. The most common predraft injuries were elbow tendinitis (n = 312), ulnar collateral ligament injury (n = 212), and shoulder labral tear (n = 76). The most common predraft treatments were physical therapy (n = 922), ulnar collateral ligament reconstruction (n = 115), and fracture fixation (n = 69). Of the 1890 players, 719 were drafted and played for at least 2 years. No difference was found among noninjured, nonoperative, and operative groups in terms of draft rank, games missed, or performance. Players with a nonoperative injury had a decreased odds ratio of being drafted (0.738; P = .017). Conclusion: More than half of the players entering the MLB reported a history of musculoskeletal injury requiring treatment, and the most commonly affected joints were the shoulder and elbow. Musculoskeletal history did not affect draft rank, short-term availability, or performance for MLB prospects.